The girls who fought crime: the untold true story of the country's first female investigator and her crime fighting squads - Eder, Mari K. (Sourcebooks, 2023)
"From corsets to crime fighting , Mae Foley challenged the patriarchal status quo by not only juggling family life, but also by forming the first female auxiliary police force in the City That Never Sleeps. After the 19th Amendment passed in 1920, Foley galvanized 2,000 women to join her "Masher Squad" and eventually became one of the first sworn officers with the NYPD. The "Masher Squad" brought down robbers and rapists, investigated the notorious 3X serial murders, and provided witness protection during the trails of the deadliest mafia bosses in the city. Foley starred down the barrel of the gun-from facing the patriarchy head on, but also quite literally-and always came out on top"--